Combining Ability Studies in Muskmelon (Cucumis melo L.) - Rukam S Tomar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
The parent Hara Madhu in E1, AMM-01-18 and AMM-02 -26 in E2 and AMM-01-18, AMM-02-26 and Hara Madhu on pooled basis exhibited positive and significant GCA effects for fruit yield per plant. Thus these three parents appeared to be good general combiners for fruit yield. Out of these parents AMM-01-18 had a good combining ability for fruit yield per plant, number of primary branches, number of fruits per plant, fruit weight, moisture content, total soluble solids, acidity and total soluble sugars on pooled basis. Specific combining ability effects for fruit yield and yield attributing traits revealed significant and positive SCA effects in fourteen crosses for number of primary branches per plant, nine for fruit length, twelve for fruit girth, ten for fruits per plant, eleven for fruit weight, nine for fruit yield per plant, eleven for flesh thickness, nine for moisture content, twenty for total soluble solids, twenty for acidity and fifteen for total soluble sugars data in the desired direction in pooled analysis. However, some crosses like AMM-01-18 x AMM-02-26, Hara Madhu x RM-50 and AMM- 01-18 x DM-1 exhibited significant SCA effects for fruit yield per plant over environments along with some of the component traits in different environments.